Educaton System of India: Its Functions, Drawbacks and Its Contribution: - (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Why is India still a developing country and what is stopping it from being a developed country? This particular question strikes me every time when I read something about India’s education system. I see India’s education system as a stumbling block towards its objectives of achieving inclusive growth. Let me inform you about certain startling facts. India is going to experience a paradox of nearly 90 million people joining the workforce but most of them will lack requiste skills and the mindset for productive employment according to a report in DNA. India has about 550 million people under the age of 25 years out of which only 11% are enrolled in tertiary institutions compared to the world average of 23%.